Janus Membrane: Buoyancy Assisted Janus Membrane Preparation by ZnO Interfacial Deposition for Water Pollution Treatment and Self‐cleaning (Adv. Mater. Interfaces 21/2019). Issue 21 (10th November 2019) - Pan, Tian‐Di; Li, Zong‐Jie; Shou, Da‐Hua; Shou, Wan; Fan, Jin‐Tu; Liu, Xuqing; Liu, Yong
Abstract : An excellent asymmetric Janus membrane, having hydrophilicity/underwater oleophobicity on one side and opposite hydrophobicity on the other side, is fabricated by leveraging the buoyancy of poly(vinylidene fluoride) nanofiber on water/air interface, for oil–water separation and organic pollutant decomposition. More details can be found in article number 1901130 by Wan Shou, Xuqing Liu, Yong Liu and co‐workers.